Coexistant extramedullary hematopoiesisin lymph node and non-hodgkin lymphoma with leukemic spill: A rare case report - Sharma, Bhavna; Gupta, Prajwala; Kumar, Vijay; Bhardwaj, Minakshi (Indian Journal of Case Reports, 2019)
Extramedullary hematopoiesis (EMH) commonly occurs in the liver and spleen. Non-hepatosplenic EMH in a lymphnode is rare and with co-existing non-Hodgkin lymphoma is even rarer. Careful screening of cytological slides is a must in order not to miss such rare cases of non-hepatosplenic EMH in lymphnodes. We hereby report a rare case of a 75-year-old male with coexisting lymphnode EMH and NHL, that too with the leukemic spill, which has never been reported before.